The Dynamics and Challenges of the Islamic Judicial System in Indonesia: A Historical Study and Institutionalization of Religious Courts - Eryandi Ray; Kamal, Tamrin; Saifullah; Asmerat, Desi; Julhadi (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2025)
The Religious Court in Indonesia is the oldest institution among Islamic institutions, having existed since the arrival of Islam in the regions that make up the Unitary State of the Republic of Indonesia. This institution has undergone a long journey from the era of Islamic sultanates to the present day. Despite experiencing ups and downs in line with political and legal dynamics, the Religious Court continues to exist and develop. This study aims to elaborate on the historical dynamics and role of the Religious Court in Indonesia’s national legal system, as well as to identify the challenges it faces in the future. The method used is qualitative descriptive with a literature review approach to collect data that is analyzed qualitatively. The results of the study indicate that the Religious Court has a long history and plays an important role in the exercise of judicial power, providing legal certainty and protection for legal issues concerning Muslims in Indonesia. The challenges ahead are to ensure legal certainty and protection, especially in cases related to Islamic economics.